A Case of Multidisciplinary Approach to Post-Radiotherapy Dilative Cardiomyopathy Undergoing Elective Cesarean Delivery: Anesthetic and Intensive Care Management - Sonnino, Chiara; Frassanito, Luciano; Zanfini, Bruno Antonio; Catarci, Stefano; Olivieri, Cristina; Ciancia, Mariano; Santantonio, Maria Teresa; Draisci, Gaetano (Cardiology and Cardiovascular Medicine, 2022)
Background: Cardiovascular diseases are the most common nonobstetric cause of maternal death. These cases became more common thanks to the improvement in cardiovascular therapies. A multidisciplinary team is necessary to manage these pregnancies. Case Report: A 32 years old women at the 25th week of gestation for acute heart failure in pre-existing left ventricular dysfunction induced by radio-chemotherapy admitted to the Coronary Unit of IRCCS Policlinico Universitario Agostino Gemelli for worsening of dyspneic symptoms and anuria not responding to diuretic therapy. At the echocardiogram: ejection fraction 30%, enlarged left atrium, systolic pulmonary arterial pressure 38 mmHg, bilateral pleural effusion, bilateral diffused pulmonary B lines. A multidisciplinary team composed by cardiologists, gynecologists, anesthesiologists, cardiac surgeons, neonatologists and bioethicists decided for an elective cesarean delivery at the 27th week of gestation in the hybrid cardio-thoracic operating theater. Anesthesia was provided by combined spinal-epidural technique under invasive continuous hemodynamic monitoring with the Edwards Lifesciences HemoSphere with Hypotension Prediction Index (HPI) and ForeSight technology (Edwards Lifesciences, Irvine, USA) through catheterization of the left radial artery. The femoral arteries were left available for extracorporeal circulation. Continuous norepinephrine infusion was started once liquor was collected in the spinal needle at a 0.1 mcg/kg/minute through a central line and was continued until the end of surgery. Fluid management consisted of a total of 200 ml of crystalloids. HPI values never reached alarm values (maximum value =10). The patient was discharged home on the 5th day after delivery with good hemodynamic compensation. The baby was intubated at birth and then gradually weaned from mechanica